2018
DOI: 10.1177/2055116918817385
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial flap to repair a pulmonary laceration in a cat with pyothorax

Abstract: Case summaryA 2-year-old female neutered domestic shorthair cat was presented for investigation of acute onset tachypnoea and dyspnoea. Pyothorax was diagnosed based on thoracic radiographs and fluid analysis. Medical treatment consisted of bilateral thoracostomy tube placement, antibiotic therapy and thoracic lavage. After 12 days of medical management infection was still present, warranting exploratory thoracotomy. At surgery, encapsulated abscesses were found in the left lung, right cranial and right middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…1,2 More recent reports describing surgery for cases of feline pyothorax, as well as necropsy and histopathology of lung tissue in cats with pyothorax, have demonstrated concurrent pneumonia and pulmonary abscess as common etiologies for pleural infection. 1,3,8,15 It has also been suggested that comorbidities such as upper respiratory tract infections or concurrent periodontal disease may precipitate the disease. 2,15 While no bite wounds were discovered in this case, he was originally adopted from a shelter so may have been at a higher risk of altercations prior to acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 More recent reports describing surgery for cases of feline pyothorax, as well as necropsy and histopathology of lung tissue in cats with pyothorax, have demonstrated concurrent pneumonia and pulmonary abscess as common etiologies for pleural infection. 1,3,8,15 It has also been suggested that comorbidities such as upper respiratory tract infections or concurrent periodontal disease may precipitate the disease. 2,15 While no bite wounds were discovered in this case, he was originally adopted from a shelter so may have been at a higher risk of altercations prior to acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…In patients that fail medical management, surgical exploratory is often recommended to identify the source of the leakage. 5,6,8 Autologous blood patches have been used in humans within the increasing frequency, as persistent air leak is one of the most common complications after pulmonary resection. Pleurodesis with whole blood has shown to be effective, painless and inexpensive in both humans and dogs.…”
Section: Investigationsmentioning
confidence: 99%